Aeolian geodiversity of the itapeva dunefield (Brazil) and geoconservation in the management of protected areas (2022)
The Itapeva dunefield is an active aeolian transgressive dunefield system and an important conservation area (PEVA State Park) in Torres-RS, Brazil. It is cataloged as a geosite and contains geoforms of scientific value for studying the sedimentary environments and paleoclimates of southern Brazil. It stands out for its esthetic, cultural, and recreational value for the development of tourism. However, the use and occupation of its surroundings developed rapidly, and the environmental problems associated with these changes make it desirable to apply the principles of coastal management with geoconservation to the region. This study characterizes the geoforms and analyzes how they have changed over time, in addition to describing some of the challenges for the geoconservation of the area. A geomorphological analysis was performed in this study, focusing on the identification and characterization of aeolian landforms and landform units present in the Itapeva dunefield. Recent satellite imagery, field observations, and photographs were used to conduct this research. The results show that the main aeolian depositional units present in the Itapeva dunefield are reversing transverse dunes, U-shaped sub-parabolic dunes, precipitation ridges, nebkhas, deflation plains, vegetated transgressive sand sheets, and foredunes. Erosional features such as blowouts occur mainly in the foredune area and/or are associated with nebkhas/remnant knobs. Understanding the importance of geoconservation within coastal management can be an important step toward the preservation of the few sectors comprising dunefields in Brazil. To benefit the Park’s sustainable development, it is prudent to promote geodiversity, geoconservation, and geotourism, incorporating these principles into coastal management.